"Eau de Rotten Eggs, " Toxic Language, and Caps for Bacterial RNA. Issue 1 (22nd January 2015) - Unknown
<x xml:space="preserve">Abstract</x> Each month, Chemistry & Biology Select highlights a selection of research reports from the recent literature. These highlights are a snapshot of interesting research done across the field of chemical biology. This month's Select highlights reports on the link between dietary restriction and hydrogen sulfide, how microbial redox metabolites act as interspecies signaling molecules, and a discovery that bacterial RNAs have a cap after all.